Impact of Reductions and Exemptions in Energy Taxes and Levies on German Industry - Anja Rosenberg; Anne Schopp; Karsten Neuhoff; Alexander Vasa (Climate Policy Initiative, 2011)
Between 2002 and 2007, Germany introduced its National Strategy for Sustainable Development and its Integrated Climate Protection Program, which both defined clear energy and climate-related objectives, setting an emissions reduction trajectory of 40% below the 1990 level by 2020. This spurred the development and refinement of a set of policies to create incentives for energy efficiency improvements, to reduce labour costs, and to raise funds to finance energy security and climate policy objectives. Special tax and levy reductions and exemptions were introduced for each policy for a transitional period. In this report, CPI presents a tool that it developed to help analyze the impact of tax exemptions and levy reductions on energy prices, which in turn impact energy efficiency and climate related goals. In developing this tool, we studied the impact of four major sets of energy policies and their related exemptions to determine the net impact on industry players, differentiated by the size of the industrial concern (as expressed by energy usage) and by the industrial sub-sector. The four energy policies are: The Environmental Tax Reform; The Combined Heat and Power Act; The EU Emission Trading Scheme; and The Renewable Energy Act.
Keywords: H25; L11; H32; 330; climate policy; economic instruments; tax exemption